DESIGN OF GREEN INDUSTRY EVALUATION SYSTEM WITH SIX SIGMA APPROACH - Nur Afia Tri Ningrum; Ishardita Pambudi Tama; Oke Oktavianty (JEMIS (Journal of Engineering & Management in Industrial System), 2025)
This research aims to design a green industry evaluation system using the Six Sigma approach to support self-assessment in manufacturing companies. The proposed framework integrates the three main dimensions of production process, waste management/emission performance, and company management into a structured evaluation system that includes relevant indicators for each dimension. The methodology used adopts the Define, Measure, Analyze, Improve, and Control (DMAIC) cycle, where each stage is designed to identify gaps, evaluate current performance, and propose systematic improvements. The validation phase was conducted using a questionnaire distributed to two respondents in a manufacturing company: a quality control officer and a manager. The results showed that the evaluation system was able to effectively assess green industry performance, with indicators reflecting the company's sustainability practices. Feedback confirmed the clarity, practicality and potential of the system to support continuous improvement. This study contributes a practical model that can be adopted by manufacturing companies to measure and improve their green industry performance to align with sustainable development goals.